Modelling of Casting Shots in Industrial Mold of High Pressure Die Casting - Mohd Rahmat, Bin A Rahman (Universiti Malaysia Sarawak (UNIMAS), 2019)
Pressure die casting process offers an economical method of producing large quantities of complex, high-tolerance parts in aluminium, magnesium, zinc and copper alloys. Long production runs have focused on the importance of obtaining good surface quality. Further improvements have been realized by paying close attention to high quality products, die designs and improved die casting practices. This research focuses on the development of die casting runner design, casting shot and the behaviour of the molten metal prior to its modification. This study attempts the introduction of mold design modification, and the investigation of the molten behaviour in the process, as to improve the quality of the casting parts manufactured. By using computational fluid dynamics analysis, the process of designing and visualizing the molten inside the cavity can be implemented for improvements. The method used in this research work is AutoCAD® 3D modelling and Solidworks® Flow Simulation. The fundamental design as well as the actual design of the casting shot has been simulated with the aid of computer flow simulation program. The actual parameters used in mass production has been applied to simulate the flow of molten aluminium of ADC 12. The results gained from the simulation are optimized to analyse the possible defects that may arise. From the fundamental study, four-runner type design casting shot showing better configuration of the temperature surface plot compared to six-runner type design. Six-runner type design casting shot have more area covered with high temperature which leads to the formation of defects compared to four-runner type design casting shot. Next, as we increase the injection velocity of the actual casting shot, result had shown that the total area of porosity had decreased. Hence, the simulation analysis is a powerful tool for engineers that can be used as a reference to improve productivity and iv quality of products, systems or processes. To verify the results obtained from the simulation, the research is then further escalated to experimental approach. The experimental approach is to further investigate the effects of modifications done towards the process parameters to the casting part manufactured, by using the actual die casting machine on site.